2017
DOI: 10.2217/epi-2017-0074
|View full text |Cite
|
Sign up to set email alerts
|

Elevated expression of a pharmacologic Polycomb signature predicts poor prognosis in gastric and breast cancer

Abstract: Aims: Polycomb Group (PcG) complexes are epigenetic repressors that silence tumor suppressive genes. Studies demonstrated that pharmacologic inhibition of PcG complexes with 3-deazaneplanocin A (DZNeP) induces cancer cell death by re-expressing silenced genes. Here, we evaluate the prognostic significance of DZNeP target genes in gastric and breast cancer.Patients & Methods/Materials: The prognostic impact of a DZNeP-regulated gene signature was investigated using the KM Plotter and cBio Portal resources conta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 41 publications
(44 reference statements)
0
5
0
Order By: Relevance
“…Elevated levels of Ezh2 protein have been reported in prostate and breast cancer (Valk-Lingbeek et al, 2004). Furthermore, recent studies have stated that Ezh2 overexpression is associated with aggressiveness and progression of different cancer types such as prostate, breast, bladder, and endometrial cancer, as well as melanoma (Bachmann et al, 2006;Clermont et al, 2017).…”
Section: Epigenetic Status In Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…Elevated levels of Ezh2 protein have been reported in prostate and breast cancer (Valk-Lingbeek et al, 2004). Furthermore, recent studies have stated that Ezh2 overexpression is associated with aggressiveness and progression of different cancer types such as prostate, breast, bladder, and endometrial cancer, as well as melanoma (Bachmann et al, 2006;Clermont et al, 2017).…”
Section: Epigenetic Status In Cancermentioning
confidence: 99%
“…The 3-deazaneplanocin A (DZNep), a small molecule inhibitor of Ezh2, decreases global H3K27 trimethylation, and its overexpression is associated with aggressiveness of several cancers such as prostate, breast, and bladder, as well as melanoma (Bachmann et al, 2006;Clermont et al, 2017). It has been shown that DZNep causes inhibition of proliferation and migration in mesothelioma (Kemp et al, 2012).…”
Section: Targeting Histone Modifications In Cancer Therapymentioning
confidence: 99%
“…[7][8][9][10] Based on gene microarray analysis, several prognostic gene signatures have also been identified in gastric cancer. 2,[11][12][13][14] However, tumor samples usually have a complex composition and tissue heterogeneity. These gene expressions (RNA)-based signatures could not accurately indicate the expression level and heterogeneity among the tumor cells and were not always consistent with the expression of proteins, which are the final executors of a biological function.…”
Section: Introductionmentioning
confidence: 99%
“…One of its most prominent mechanisms of action is the silencing of many cancer-related genes, thereby promoting histone H3 lysine 27 trimethylation (H3K27me3) of target gene promoters [9]. Recently, reports have shown EZH2 frequently overexpressed in several human epithelial cancers, including prostate cancer [10], breast cancer [11], gastric cancer [11], non-small-cell lung cancer [12], esophageal cancer [13], melanomas [9], oral cancer [14], and endometrial carcinomas [15]; it is additionally associated with increased tumor cell proliferation and exacerbated outcomes [16]. 3-Deazaneplanocin A (DZNep) reportedly downregulates EZH2 and inhibits H3K27me3 [17].…”
Section: Introductionmentioning
confidence: 99%